Justifying anti-doping: The fair opportunity principle and the biology of performance enhancement - Loland, S.; Hoppeler, H. (European Journal of Sport Science, 2012)
Doping is a complex moral and scientific dilemma and its prevention has led to a costly but less than perfect control system implemented worldwide by the World Anti-doping Agency (WADA). For a substance or method to be considered for the WADA Prohibited List, three criteria must be met: (1) the substance or method has the potential to enhance, or enhances, sport performance; (2) use of the substance or method represents an actual or potential health risk to the athlete; and (3) use of the substance or method violates the "spirit of sport". The "spirit of sport" is defined as "the celebration of the human spirit, body and mind" and explained with reference to a series of ideal values: ethics, fair play, and honesty; health; excellence in performance; character and education; fun and enjoyment; teamwork; dedication and commitment; respect for rules and laws; respect for self and other participants; courage; community and solidarity. These values do not lend themselves to clear-cut interpretation and are of little help in drawing unambiguous lines in concrete cases. A proposal is made of how to interpret the "spirit of sport" in more precise ways in terms of a combination of the fair opportunity principle and a biological and evolutionary understanding of athletic performance as a result of the systematic utilization of the phenotypic plasticity of the human organism. The argument is that such understanding improves significantly the possibilities for drawing of lines when it comes to doping issues.